Feeding Traits and Body Dimensions of Lime and Parkote Buffaloes Raised by Small-Scale Farms in Kaski, Nepal (Journal of Buffalo Science, 2017)
Thirty farms that raised Lime or Parkote female buffaloes in Kaski were selected for the survey of animal census, feeding traits and body dimensions in the rainy season and the dry season. The average number per farm was 0.76 in Lime and 0.27 in Parkote. The average of age and parity was 8.2 years old and 4.4 in Lime, and 6.6 years old and 2.8 in Parkote, respectively. The mean dry matter (DM) supply of roughage, supplemental feed and total feed was higher in the dry season than in the rainy season (11.8 kg/head/day vs. 10.3 kg/head/day, 1.2 kg/head/day vs. 0.8 kg/head/day, 13.0 kg/head/day vs. 11.1 kg/head/day, respectively, P